(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the basic aspects of research of the proper names in artistic texts are reflected. The purpose of this investigation is research of common onomastic’s units in works of Ukrainian writers-fantasies, who were not under intent attention of researchers until now.